Gender differentials in preventive health care: Incidences and determinants among Pakistani children - Faham Masud; Shujaat Farooq (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
In this study, an attempt has been made to estimate gender health differential with a focus on preventive health care. Using the Pakistan Demographic Health Survey (PDHS) of 2006-07, the study has targeted the children of age 12-23 months and found substantial sex differences in the immunization status of children where boys are more immunized than girls, reflecting gender biasness over preventive health provision. Through bi-variate and multi-variate analysis, the study found that a variety of factors, including individual, socio-demographic and economic factors are causing this dilemma. Mother's characteristics including age, literacy and headship of the household significantly affect the immunization status of the children. Similarly, the socio-economic status of the household including income, household size, structure and gender of the head of the households are also the key determinants of preventive health care differentials. Across the provinces, the variation of coverage and discrimination is also evident with more coverage in Punjab and least in Baluchistan.
Keywords: 330; Human Health; Children; Child care; Discrimination; Kinder; Gesundheitsvorsorge; Geschlechterdiskriminierung; Pakistan